2016
DOI: 10.2214/ajr.16.16630
|View full text |Cite
|
Sign up to set email alerts
|

Can MDCT Unmask Instability in Binder-Stabilized Pelvic Ring Disruptions?

Abstract: Evaluation for avulsive signs improves MDCT sensitivity for the detection of rotational instability but not vertical instability in patients with binders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
0
13
0
7
Order By: Relevance
“…Predictor variable selection.-Candidate predictor variables were selected on the basis of clinical practicality and scientific evidence (2,(12)(13)(14)(15)(16)(18)(19)(20)(21)(22)(23)(24) in consultation with two orthopedic trauma surgeons with nationally recognized expertise in pelvic trauma (J.W.N., R.V.O.). CT predictors shown to be associated with major vascular injury include ICE and segmented pelvic hematoma volumes (2,(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictor variable selection.-Candidate predictor variables were selected on the basis of clinical practicality and scientific evidence (2,(12)(13)(14)(15)(16)(18)(19)(20)(21)(22)(23)(24) in consultation with two orthopedic trauma surgeons with nationally recognized expertise in pelvic trauma (J.W.N., R.V.O.). CT predictors shown to be associated with major vascular injury include ICE and segmented pelvic hematoma volumes (2,(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…is more likely with wide fracture gaps (approximately 5 mm or greater); with comminution; and with pubic symphysis diastasis, which is indicative of mechanical instability (9,12,(18)(19)(20). The Tile classification provides an overall impression of mechanical instability on the basis of qualitative CT findings (21)(22)(23)25).…”
Section: Scanning Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, patients with PCCDs in place while undergoing CT (63%) were included in the present study. It has been shown previously that the presence of PCCDs may lead to misinterpretation of the fracture pattern and thus have an influence on fracture classification [46][47][48] and assessment of pelvic ring stability [49]. However, given the widespread use of PCCDs in the prehospital setting [50], this situation is now frequently encountered and represents clinical conditions under which fracture classifications have to occur.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…A retrospective review of the CT imaging while the binder was still in place showed some signs that may have indicated a more serious injury than initially suspected, such as the pelvic hematoma, a small avulsion fracture at the pubic symphysis (Figure 1B) and a subtle widening of the left sacroiliac joint on the initial CT imaging (Figure 1C). 1 Local pre-hospital guidelines state that a binder should be applied if there is suspicion of a pelvic injury after blunt high-energy trauma with hemodynamic instability (or systolic blood pressure < 110 mm Hg). 2 Serious pelvic injuries may be missed in the presence of a well-applied pelvic binder, 3 which is particularly true for purely ligamentous anteroposterior compression injuries.…”
mentioning
confidence: 99%